2007
DOI: 10.1177/1367493507073060
|View full text |Cite
|
Sign up to set email alerts
|

Caring for a child with Juvenile Huntington’s Disease: helpful and unhelpful support

Abstract: There has been little research into the psychosocial impact of Juvenile Huntington's Disease on the child and family. This study investigates the social and health care needs of those affected by Juvenile Huntington's Disease. Ten semi-structured interviews with carers were analysed using the qualitative methodology interpretative phenomenological analysis. This article reports three themes on the social support that families received. The first theme describes how parents perceived the support that they recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 8 publications
0
32
0
1
Order By: Relevance
“…Family problems are connected with less support from loved ones. It should also be remembered that the parents of children with EB perceive the support they get differently [12], and they sometimes see it as a source of stress. The above data are consistent with the results obtained for the model of life satisfaction (Table 4), in which also the information support from family and the severity of the child's disease were found to be variables of significant influence on the sense of life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Family problems are connected with less support from loved ones. It should also be remembered that the parents of children with EB perceive the support they get differently [12], and they sometimes see it as a source of stress. The above data are consistent with the results obtained for the model of life satisfaction (Table 4), in which also the information support from family and the severity of the child's disease were found to be variables of significant influence on the sense of life satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…Each situation affects the parents of ill children differently. Taking care of an incurably ill child often puts a parent in a hard situation and requires an assessment of the child's needs at every stage of being with it [12][13][14][15][16]. In the case of EB, there are practically no such studies at all.…”
mentioning
confidence: 99%
“…Key findings included: how families experienced isolation and a lack of understanding about JHD; how many parents were aware that something was wrong with their child; and perceptions of helpful and unhelpful forms of social support from families, friends and health-care professionals. [11][12][13] The study reported here aims to develop and extend the existing understanding of the personal experience of families living with a child with JHD; how they think, feel and manage the challenges that face them. The study recruited parents from four European countries: Italy, The Netherlands, Poland and Sweden.…”
Section: Introductionmentioning
confidence: 99%
“…IPA has been employed in a number of studies examining psychosocial issues in genetics (see, eg, references [15][16][17] in addition to the previous work on JHD. [11][12][13] …”
Section: Introductionmentioning
confidence: 99%
“…Para os autores, os esforços que se têm feito para entender as necessidades em saúde mental dessas crianças têm sido problemáticos pelas limitações metodológicas: a maioria dos estudos se fundamenta em informações dos pais sobre o comportamento da criança e pouco se conhece sobre a percepção das pró-prias crianças. Porém sabe-se que a opinião dos pais tem importante viés, especialmente pelo fato de que muitos progenitores de crianças doentes crônicas apresentam comportamentos superprotetores (Gartstein et al, 2000;Remor, Ulla, Ramos, Arranz, & Hernández-Navarro, 2003), dispõem de pouco apoio social (Brewer et al, 2007) e tem riscos de apresentarem estresse pós-traumá-tico (Farley et al, 2007;Young et al, 2003).…”
unclassified